Yeast Concentration, pH, and Fermentation Time on the Production and Concentration of Bioethanol Made from Sargassum crassifolium as a Renewable Energy Source - Tuaputty, Hasan (Biosel Biology Science and Education, 2020)
Sargassum crassifolium is one type of brown algae which has many benefits and has a high economic value. It has a relatively short harvest age. It is widespread in Indonesia's marine waters with high production potential, but the production is still largely from the harvest of natural supplies. Sargassum contains a lot of alginate polysaccharides that are used for food-beverage, cosmetics, and pharmaceutical industries. In addition, it also contains other types of polysaccharides namely cellulose (part of the cell wall), manithol (as stored carbohydrates) and fucoidan. The cellulose content in Sargassum ranges from 23.97 to 35.22%. Thus, it can be processed into a raw material in the production of bioethanol. The results of the research showed that the yeast concentration 3%, the medium pH 7, and fermentation time 72 hours gave the best results in increasing the production and content of bioethanol made from Sargassum crasifolium.